How Economic Analysis Increases the Awareness of Clinical Services: A Case of Diabetes Mellitus at a Teaching Hospital in Myanmar - Wah Wah Khaing Oo (2022)
Objectives: Myanmar faces a growing epidemic of type 2 diabetes mellitus, which has significant impact on the individual health and health service system; nevertheless, reliable cost estimate for treating diabetes is still unknown. Therefore, this study aimed to explore the treatment cost of hospitalization by type 2 diabetes mellitus and the association of complications and comorbidities with the treatment cost. Methods: The retrospective incidence-based cost of illness analysis was performed at the diabetes ward of 800-bed teaching hospital in Yangon, Myanmar. The data were retrieved from hospital financial reports and patient's medical records for the fiscal year 2017 to 2018. Data was analyzed by using descriptive statistics and multivariate statistics. One-way sensitivity analysis was used to assess the uncertainty of input parameters. Results: This study involved 87 inpatients with type 2 diabetes mellitus with an average length of stay of 16.1 ± 12.6 days. Of the study sample, 67% had complications whereas 74% had comorbidities. The average treatment cost per admission was $718.7 (equal to 58% of gross domestic product - GDP per capita) at 2018 prices. Based on the multiple regression analysis, cost savings per admission were $276.5, $307.3, and $319.5 from preventing foot ulcer, nephropathy, and retinopathy, respectively. Conclusions: This study found that the treatment of diabetes is costly because of its preventable health consequences. Better disease management to prevent complications results in considerable cost savings. This quantitative evidence would increase awareness in health service system.